2022
DOI: 10.1029/2022gl098162
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of P Wave From Ambient Seafloor Noise Observed by Distributed Acoustic Sensing

Abstract: Distributed acoustic sensing (DAS) using fiber optic cables is currently a powerful tool for detecting signals of various wave propagations, because the station density along a cable is higher than the typical density of seismic observations using individual seismic sensors. For example, DAS on land is capable of observing signals from regional (Lindsey et al., 2017) and teleseismic earthquakes (Yu et al., 2019) and can estimate shallow S-wave velocity (Vs) structure from ambient noise records (Ajo-Franklin et… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This suggests that we can stack adjacent traces in space without introducing bias to the recorded wavefield, in order to increase the SNR of the data. In the context of ambient noise interferometry, spatial stacking of large‐N arrays and DAS has been successfully applied to improve the stability of retrieved Green's functions, for example, in order to reveal body waves in cross‐correlations (e.g., Lin et al., 2013; Nakata et al., 2015; Tonegawa et al., 2022; Wang et al., 2014) and improve surface wave dispersion measurements (e.g., Cheng et al., 2023; Czarny & Zhu, 2022; Jousset et al., 2022; Li et al., 2022; Shragge et al., 2021). It is important to emphasize that we measure velocity changes in the coda of cross‐correlations.…”
Section: Exploiting the Spatial Resolution Of Dasmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that we can stack adjacent traces in space without introducing bias to the recorded wavefield, in order to increase the SNR of the data. In the context of ambient noise interferometry, spatial stacking of large‐N arrays and DAS has been successfully applied to improve the stability of retrieved Green's functions, for example, in order to reveal body waves in cross‐correlations (e.g., Lin et al., 2013; Nakata et al., 2015; Tonegawa et al., 2022; Wang et al., 2014) and improve surface wave dispersion measurements (e.g., Cheng et al., 2023; Czarny & Zhu, 2022; Jousset et al., 2022; Li et al., 2022; Shragge et al., 2021). It is important to emphasize that we measure velocity changes in the coda of cross‐correlations.…”
Section: Exploiting the Spatial Resolution Of Dasmentioning
confidence: 99%
“…In multiple studies, it has been shown that DAS resolves structure and dynamics of the sub-surface at unprecedented spatial resolution and at low cost compared to conventional seismometers (e.g., Diaz-Meza et al, 2023;Jousset et al, 2018Jousset et al, , 2022Lindsey et al, 2019;Williams et al, 2019;Zhan, 2019). In the context of ambient noise, DAS has been applied to obtain dispersion curves (e.g., Dou et al, 2017;Luo et al, 2020;Shao et al, 2022;Song et al, 2022;Zhou et al, 2022) and extract body waves through cross-correlation (Tonegawa et al, 2022). Velocity changes caused by ground water fluctuations were tracked along a DAS cable near the Sacramento river in the US (Rodríguez Tribaldos & Ajo-Franklin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With a high density of channels along the cable, the distributed acoustic sensing (DAS) technique can monitor the horizontal component of strain along the cable direction, which allows us to investigate the spatial variation of wavefields in detail, including on seafloor telecom cables (Lindsey et al., 2019; Sladen et al., 2019; Williams et al., 2019). This technique has been widely used in marine geophysics for sensing distances of 50–120 km from coastlines to investigate seismological subseafloor structures (Cheng et al., 2021; Fukushima et al., 2022; Lior et al., 2022; Spica et al., 2020; Tonegawa et al., 2022; Viens et al., 2022, 2023), hydroacoustic waves (Matsumoto et al., 2021), Scholte wave generation (Spica et al., 2022), ocean surface gravity waves (Williams et al., 2019), and shallow slow earthquakes (Baba et al., 2023). Ocean DAS records were also uploaded to a repository (Spica et al., 2023) as part of a project that collected DAS data for teleseismic events that occurred in February 2023 (Wuestefeld & Wilks, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, distributed acoustic sensing (DAS) measurement has been widely used for the observations of regular earthquakes (e.g., Lindsey et al., 2017; Shinohara et al., 2022; Zhan, 2019), infragravity waves (Williams et al., 2019), hydroacoustic signals (Matsumoto et al., 2021), and the extraction of P ‐waves from ambient noise (Tonegawa et al., 2022). DAS measurements use an optic fiber cable as a strain or strain rate sensor array.…”
Section: Introductionmentioning
confidence: 99%